STRATEGI FUNDRAISING DANA ZAKAT PADA BAZNAS KABUPATEN TANAH DATAR - NOPIARDO, WIDI (IAIN Batusangkar, 2017)
Fundraising activities are essential for the operation of zakat management programs and its operations. In BAZNAS, Tanah Datarregency, it is found that in 2013, the total of zakat fundraising is Rp.8.418.272.757, -, 2014 the total of zakat fundraising is Rp. 8.754.155.665,-, 2015 the total is Rp. 9.179.036.735,-, 2016 the total is Rp. 11.148.298.358,-. While for the following years, it increases signi?icantly. In 2014, Zakat fundraising was enhanced 3.99% with Rp. 335.882.908. It was from Rp.8.418.272.757 to Rp.8.754.155.665. It also increased 4.85% with Rp. 424.881.070 in 2015. It was from Rp.8.754.155.665to Rp.9.179.036.735. It also significantly boosted in 2016 for 21.45% with Rp. 1.969.261.623. It was from Rp.9.179.036.735 to Rp. 11.148.298.358. These facts indicate a precise strategy used by BAZNAS, Tanah Datarregency in doing zakat fundraising. This type of research was field research with qualitative descriptive approach. Data were collected through interviews, documentation, and literature study. The results showed that BAZNAS, Tanah Datar regency used strategy direct and indirect fundraising. If the muzakki have expressed their willingness to pay zakat through media campaigns and direct fundraising, BAZNAS, Tanah Datar regencyused three ways to ease the muzakki to pay their zakat. First, do direct cutting through UPZ which has been formed to be deposited into the account of BAZNAS Tanah Datar. Second, do